2019
DOI: 10.1371/journal.pcbi.1007495
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of combination GM-CSF immunotherapy and oncolytic virotherapy success identified through in silico treatment personalization

Abstract: Oncolytic virotherapies, including the modified herpes simplex virus talimogene laherparepvec (T-VEC), have shown great promise as potent instigators of anti-tumour immune effects. The OPTiM trial, in particular, demonstrated the superior anti-cancer effects of T-VEC as compared to systemic immunotherapy treatment using exogenous administration of granulocyte-macrophage colony-stimulating factor (GM-CSF). Theoretically, a combined approach leveraging exogenous cytokine immunotherapy and oncolytic virotherapy w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 40 publications
(63 reference statements)
1
58
0
Order By: Relevance
“…Notably, the predictions of anti-tumor response and predictive biomarkers are strongly affected by our assumptions on mechanism of action for all therapeutics and distribution of physiological parameters for virtual patient cohort (Cassidy and Craig, 2019). The expected response rate of the ongoing clinical trial simulated in this study, as suggested by the 95% percentile bootstrap confidence intervals, could fall into a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the predictions of anti-tumor response and predictive biomarkers are strongly affected by our assumptions on mechanism of action for all therapeutics and distribution of physiological parameters for virtual patient cohort (Cassidy and Craig, 2019). The expected response rate of the ongoing clinical trial simulated in this study, as suggested by the 95% percentile bootstrap confidence intervals, could fall into a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of oncolytic virus therapy is to directly kill the tumor cells as well as activate the anti-tumor immune response [28]. Genetically engineered recombinant oncolytic viruses have also been designed in order to improve antitumor activity [29]. However, this strategy is limited by the small viral genomes and technical di culty.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic algorithms are heuristic global optimisation routines inspired by natural selection that are frequently employed to estimate parameters in computational biology models. They have previously been applied to study optimal dosing routines in immunology [54,55] and combined oncolytic virotherapy and immunotherapy [29].…”
Section: Implementing a Genetic Algorithm To Determine The True Optimmentioning
confidence: 99%
“…Deterministic systems of ordinary differential equations (ODEs) are used to describe the key biophysical interactions and are then analysed to determine optimal therapeutic protocols [23]. In oncology, these techniques have been used to successfully optimise chemotherapy and immunotherapy treatment [25][26][27][28][29][30]. Zhu et al [31] optimised the scheduling of one cycle of chemotherapy drug VP-16 and found a new optimal drug regime which improved the clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation